Cell-free protein synthesis: biomedical applications and future perspectives - Monck,C; Elani,Y; Ceroni,F (Chemical Engineering Research and Design, 2022)
The use of cell-free protein synthesis (CFPS) has become increasingly widespread in synthetic biology over recent years, providing an effective platform for the study and engineering of cellular processes. The versatility and portability of CFPS systems have also boosted their potential for usage outside of the laboratory in a wide number of applications, from construct prototyping to bioproduction. CFPS is particularly well suited to biomedical applications, such as the production of clinical molecules and vaccines. It can also be integrated with additional technologies such as microfluidics and liposomal encapsulation to provide a new route for on-demand therapeutic expression. In this review we outline the key features of CFPS that make it a powerful platform for biomedical applications. We also discuss existing limitations with respect to the use of CFPS in the production of complex protein products and the limited production capacity of current systems. Addressing these will be integral in expanding the application of CFPS in biotherapy